Runtime Assertion Checking. - Clarke, Lori A.; Rosenblum, David S. (Computer (00189162), 2008)
The article focuses on a report that describes the importance of runtime assertion checking. Assertions are considered as one of the most useful automated techniques available for detecting faults and providing information about their locations. The report claims that assertions have a long history in the annals of software engineering and programming language design. The important contributions of several individuals to computer programming, including Herman H. Goldstine, Konrad Zuse and John von Neumann, are also discussed.